The capital structure: Government-Linked and Non- Government-Linked Companies in the trading and services industry in Malaysia / Wahida Ahmad, Noor Sharida Badri Shah and Noor Hafizha Muhamad Yusuf - Ahmad, Wahida; Badri Shah, Noor Sharida; Muhamad Yusuf, Noor Hafizha (Universiti Teknologi MARA, Perlis, 2017)
Government-Linked Companies perhaps differ from other companies in terms of their capability to absorb socio- political benefit from the government interest. This allows the companies to take greater risk with respect to their capital structure decision. The paper seeks to identify if there are differences in capital structure between Malaysian Government-Linked Companies (GLCs) and Non-Government-Linked Companies (NGLCs). The sample consists of six companies each of the GLCs and the NGLCs, all from trading and services industry. The study uses 21 years of unbalanced panel data from 1993 to 2013. Leverage acts as dependent variable, while profitability, asset tangibility, firm size, and growth are the independent variables. The model uses group dummy to distinguish the sample of GLCs and NGLCs. Within the scope of the study, the paper is unable to proof any differences in capital structure between the two groups of companies. The random effects estimation identify profitability as negatively significant with capital structure decision for GLCs and NGLCs. In contrast, asset tangibility and firm size are positively related to leverage. The interaction effect discloses company growth have a different impact on leverage for GLCs and NGLCs for trading and services companies in Malaysia.